Taxonomic reappraisal of the sphagesaurid crocodyliform Sphagesaurus montealtensis from the Late Cretaceous Adamantina Formation of São Paulo State, Brazil - Iori, Fabiano Vidoi; Marinho, Thiago Da Silva; Carvalho, Ismar De Souza; Campos, Antonio Celso De Arruda (Zootaxa, 2013)
Sphagesaurus montealtensis is a sphagesaurid whose original description was based on a comparison with Sphagesaurus huenei, the only species of the clade described to that date. Better preparation of the holotype and the discovery of a new specimen have allowed the review of some characteristics and the identification of several synapomorphies of S. montealtensis with the genus Caipirasuchus: presence of antorbital fenestra; external nares bordered only by the premaxillae; premaxilla with four teeth and one diastema (between the 3rd–4th teeth); one diastema between the 4th premaxillary tooth and the 1st maxillary tooth; dentary with ten teeth and two diastemata (between the 4th–5th and 5th – 6th teeth); nasal with a groove parallel to the suture with the frontal bone; nasal long, with an acute anterior margin touching anterolaterally the premaxilla, jugal is a straight bar in the lateral view; frontal is longer than wide; a dorsoventrally expanded and vertically oriented quadrate with a groove separating the medial and lateral condyles; the frontal has a discrete sagittal crest; dentary with six posterior sphagesauriform teeth and four anterior conical teeth, the first three are the smallest of the series and the fourth is slightly laterally compressed. The referral of S. montealtensis to the genus Caipirasuchus, as Caipirasuchus montealtensis comb. nov. is proposed here, based on the new taxonomic observations and the results of a phylogenetic analysis.